Iowa RBA, January 11, 1999 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1999)
Email for the Iowa RBA for January 11, 1999. Highlights include Spotted Towhee, White-winged Scoter, Long-tailed Duck, and Prairie Falcon. Includes notes for updates for January 12, January 13, and January 15. Epson - sheet feed/flatbed